Einstellungen der Bevölkerung zum Greening der Gemeinsamen Agrarpolitik: Ergebnisse einer Panel-Befragung; Citizens' Attitudes towards Greening as Part of Common Agricultural Policy: Results of a Panel Survey - Lara Beer; Heinke Heise (German Journal of Agricultural Economics (GJAE), 2020)
– Modern agriculture is increasingly in the focus of the critical public regarding its too low environmental sustainability. The so-called Greening was introduced as an additional policy tool into the current Common Agricultural Policy (CAP) for providing incentives for more environmental protection. The Greening is expected to contribute to the implementation of a more environmental and climate friendly land management. To socially and politically justify support programmes for environmental protection, it is important to identify citizens' attitudes towards such programmes. So far, only studies regarding citizens' attitudes towards the GAP in general exist but no studies regarding environmental measures such as pillar 2 measures or Greening exist. To close this research gap, this paper seeks to analyse German citizens' attitudes towards the Greening with the help of a cluster analysis. Our analysis of a panel-data set with 499 participants shows that citizens support the Greening in total. However, attitudes diverge regarding remuneration of environmental benefits as well as tightening Greening requirements.
Keywords: 330